Screening of presumptive amylase-producing bacillus bacteria isolated from soil containing dairy food waste / Nur Insyirah Amanina Shalehudin, Maimunah Mustakim - Shalehudin, Nur Insyirah Amanina; Mustakim, Maimunah (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Soil microorganisms can produce amylase, especially the Bacillus strains bacteria. Amylase- Healthscope 2022, Vol 5(1): 75-79 producing bacteria can be obtained from soil containing properly composted dairy food waste. This study aims to analyse amylase-producing bacteria obtained from soil contaminated with dairy food waste. The soil sample was collected in three different settings, which were A: normal soil without food waste, B: soil with yoghurt-based dairy food waste and C: soil with mixed dairy food waste. The isolation of bacteria was done and screened for α-amylase-producing bacteria using a starch hydrolysis test. Based on the result, a total of 17 gram-positive isolates were identified. They were classified into spore-forming and catalase-positive bacteria. Nevertheless, seven out of 17 isolates showed a positive for amylase production. Presumptive identification of the soil sample showed that soil A contains amylase-producing bacteria, presumably non-Bacillus spp. In contrast, soil samples B and C, which after being contaminated with dairy food waste, contain amylaseproducing bacteria, most likely Bacillus spp. As exhibited by the characteristics of isolates B1, B3, B7, and C3. In conclusion, the amylase-producing bacteria from soil contaminated with dairy food waste were identified and classified.